On a method for investigation of random oscillations of the linear visco-elastic system - Khiem, Nguyen Tien; Anh, Nguyen Dong (Vietnam Journal of Mechanics, 1979)
The paper deals with the method for investigation of the random excited integro-differential equations, appeared frequently in the theory of the visco-elastic system. By this method the linear random excited integro-differential equations can be approximated by a linear random excited differential one. In the case of non-random excited systems the results coincide with the ones obtained by averaging method’ for the determined integro-differential equations.